Phraseological Units as a Means of Creating Comic Effect in Yu. Buyda’s Book of Stories “Prussian Bride” - K. A. Degtyarenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article considers individual author’s methods of structural and semantic transformation of phraseological units in Yu. Buyda’s book of stories. Transformations of this type in Yu. Buyga’s works include the following techniques: wedging, adding, lexical replacement, removal of idiom on the level of subtext. The essence of the game technique is to restore the original, direct meaning of the lexemes constituting a phraseological unit. This is achieved by playing out such characteristic features of phraseological units as the constancy of the lexical composition, the impermeability of the structure of phraseological units, the limited ability to combine with other elements of the text and attach dependent words. It is revealed that in the texts of Yu. Buyda this technique is implemented by introducing variables (occasional) lexical components in the updated structure of the idiom, grammatical transformations, as well as fixed order violations. As new, variable components the author uses lexemes of the same thematic area or those motivated by logical, intra-text and inter-text connections. The transformed phraseology unit actualizes the original appearance and meaning of the usual idiom. The paper shows that projecting the transformed phraseology on a contrast background created by the original unit generates a meaningful multiplicity, which is intended to create a comic effect. The discovery of new, hidden meanings is an inexhaustible source of comic. The originality of the phenomenon of language game, exploiting the technique of punish phraseology, which consists in the creation of layered polysemy, is demonstrated. The technique is not limited by the game of figurative and direct meanings of phraseology unit, but develops entire semantic series, providing several alternative game variants of interpretation.